Robust coupling of angiogenesis and osteogenesis by VEGF-decorated matrices for bone regeneration. (1st September 2022) - Burger, Maximilian G.; Grosso, Andrea; Briquez, Priscilla S.; Born, Gordian M.E.; Lunger, Alexander; Schrenk, Flavio; Todorov, Atanas; Sacchi, Veronica; Hubbell, Jeffrey A.; Schaefer, Dirk J.; Banfi, Andrea; Di Maggio, Nunzia
Abstract: Rapid vascularization of clinical-size bone grafts is an unsolved challenge in regenerative medicine. Vascular endothelial growth factor-A (VEGF) is the master regulator of angiogenesis. Its over-expression by genetically modified human osteoprogenitors has been previously evaluated to drive vascularization in osteogenic grafts, but has been observed to cause paradoxical bone loss through excessive osteoclast recruitment. However, during bone development angiogenesis and osteogenesis are physiologically coupled by VEGF expression. Here we investigated whether the mode of VEGF delivery may be a key to recapitulate its physiological function. VEGF activity requires binding to the extracellular matrix, and heterogeneous levels of expression lead to localized microenvironments of excessive dose. Therefore we hypothesized that a homogeneous distribution of matrix-associated factor in the microenvironment may enable efficient coupling of angiogenesis and bone formation. This was achieved by decorating fibrin matrices with a cross-linkable engineered version of VEGF (TG-VEGF) that is released only by enzymatic cleavage by invading cells. In ectopic grafts, both TG-VEGF and VEGF-expressing progenitors similarly improved vascularization within the first week, but efficient bone formation was possible only in the factor-decorated matrices, whereas heterogenous, cell-based VEGF expression caused significant bone loss. In critical-size orthotopic calvaria defects, TG-VEGF effectively improved early vascular invasion, osteoprogenitor survival and differentiation, as well as bone repair compared to both controls and VEGF-expressing progenitors. In conclusion, homogenous distribution of matrix-associated VEGF protein preserves the physiological coupling of angiogenesis and osteogenesis, providing an attractive and clinically applicable strategy to engineer vascularized bone. Statement of significance: The therapeutic regeneration of vascularized bone is an unsolved challenge in regenerative medicine. Stimulation of blood vessel growth by over-expression of VEGF has been associated with paradoxical bone loss, whereas angiogenesis and osteogenesis are physiologically coupled by VEGF during development. Here we found that controlling the distribution of VEGF dose in an osteogenic graft is key to recapitulate its physiological function. In fact, homogeneous decoration of fibrin matrices with engineered VEGF could improve both vascularization and bone formation in orthotopic critical-size defects, dispensing with the need for combined osteogenic factor delivery. VEGF-decorated fibrin matrices provide a readily translatable platform for engineering a controlled microenvironment for bone regeneration. Graphical abstract: Image, graphical abstract